2014
DOI: 10.1016/j.ygyno.2013.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of α4β1 integrin increases ovarian cancer response to carboplatin

Abstract: Objective The inability to successfully treat women with ovarian cancer is due to the presence of metastatic disease at diagnosis and the development of platinum resistance. Ovarian cancer metastasizes throughout the peritoneal cavity by attaching to and invading through the mesothelium lining the peritoneum using a mechanism that involves α4β1 integrin and its ligand (vascular cell adhesion molecule) VCAM-1. Integrin α4β1 expression on tumor cells is known to confer protection from therapy in other cancers, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Indeed, natalizumab inhibits binding of leukocytes to vascular endothelial cell adhesion molecule 1 (VCAM‐1) by blocking α 4 β 1 or α 4 β 7 integrin receptors on leukocytes. This may be a potential therapeutic target to influence chemotherapy responsiveness in resistant disease 17, 18, 19…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, natalizumab inhibits binding of leukocytes to vascular endothelial cell adhesion molecule 1 (VCAM‐1) by blocking α 4 β 1 or α 4 β 7 integrin receptors on leukocytes. This may be a potential therapeutic target to influence chemotherapy responsiveness in resistant disease 17, 18, 19…”
Section: Discussionmentioning
confidence: 99%
“…High levels of β1 integrin correlate with lower survival rates in patients with invasive breast cancer . β1 integrin‐deficient MDA‐MB‐231 cells acquired more epithelial‐like morphologies and features in human triple negative breast cancer …”
Section: Discussionmentioning
confidence: 99%
“…(24) b1 integrin-deficient MDA-MB-231 cells acquired more epithelial-like morphologies and features in human triple negative breast cancer. (25) We also performed knockdown of Ets-1 by using the siRNA. Our findings demonstrated that knockdown of Ets-1 resulted in decreased expression of Ets-1 and b1 integrin in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Natalizumab, an antibody targeting α4β1 integrin, can overcome the protection of microenvironment to malignant B-cells from rituximabinduced apoptosis [154]. The combination of carboplatin and anti-α4β1 integrin antibodies results in increased ovarian cancer cell death and doubling time in vitro and significantly reduces tumor burden in murine models of platinum-resistant peritoneal disease [155]. Integrin α4 blockade sensitizes resistant human leukemia blasts to acute lymphoblastic leukemia (ALL) chemotherapy (vincristine, dexamethasone, and L-asparaginase) in vitro and its addition to standard ALL chemotherapy prolongs the survival of NOD/SCID recipients of human pre-B ALL cells in vivo [156].…”
Section: Integrins and Cell Adhesion-mediated Drug Resistancementioning
confidence: 99%